IoT Enabled Smart Agriculture Monitoring and Water Pumping Control System using BLYNK Server - RAJARAM,KAMATCHI,THAMIZHKANII, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The aim of proposed project is to implement real time atomization of Modern Agricultural System using IOT protocol method. These projects ensure the pumping system in agricultural sector to be a valuable process with low cost, low power, efficiency, compactness, etc. In this project, Wireless sensor network (IOT) have been developed for environmental agricultural monitoring and management of the crop field. Wireless nodes developed were capable of transmitting environmental measurements at scheduled intervals. The data from a network of these sensors could be used to vastly improve agriculture management and environmental protection practices through a more accurate modelling of crop-growth, hydrologic flow and carbon-nutrient cycling processes. This system was designed to monitor the status of temperature, humidity and soil moisture using android mobile phone. The IOT does not require any external power supply as it obtains its energy from a solar panel which is a renewable source of energy. Various nodes in different places are connected via IOT which transmits and receive the data in a node that transmits the status of the crop field to the user through IoT (blynk server) to control the pumping system.